From traitor to zealot: exploring the phenomenon of side-switching in extremism and terrorism - Koehler, Daniel (Cambridge University Press, 2022)
"What makes a neo-Nazi become a convinced anti-fascist or a radical left-winger become a devout Salafist? How do they manage to fit into their new environment and gain acceptance as a former enemy? The people featured in this book made highly puzzling journeys, first venturing into extremist milieus and then deciding to switch to the opposite side. By using their extraordinary life stories and their own narratives, this book provides the first in-depth analysis of how and why people move between seemingly opposing extremist environments that can sometimes overlap and influence each other. It aims to understand how these extremists manage to convince their new group that they can be trusted, which also allows us to dive deep into the psychology of extremism and terrorism. This fascinating work will be of immense value to those studying radicalization and counter-radicalization in terrorism studies, social psychology, and political science"--